An analysis of Malaysian English monophthongs by Kelantan dialect speakers / Nur Izyan Izzati Nazilan - Nur Izyan Izzati , Nazilan (2019)

(untitled)
This research provides an acoustic analysis of the English monophthongs produced by the Kelantanese dialect speakers; 5 female participants from a secondary school in Tumpat, Kelantan. The speakers were asked to produce 8 monophthongs [ɛ, u, o, ɔ, ə, i, e, a] of Kelantan Dialect and 12 monophthongs [i, ɪ, ɛ, æ, a, ə, u, ʊ, ɔ, ʌ, ɒ, ɑ] of English language. Words list, sentences and a short text in both Kelantan Dialect and English language were used in data collection. This paper aims to analyze the acoustic patterns of Kelantan Dialect and Malaysian English’s vowels as produced by the Kelantanese participants. In addition, this paper also focuses to understand the vowel contrasts in terms of vowel quality and vowel length of Kelantan Dialect and Malaysian English monophthongs pronunciation. The finding of the study shows there are similarities and differences in the vowel quality of the English monophthongs produced by the Kelantanese speakers and other speakers of Malaysian English. However, the acoustic analysis done on the vowels produced by the participants did not show any influence of the dialect. Besides that, it is clear that English language used among Kelantan Dialect speakers are still in the early third phase; nativization of Schneider’s Dynamic Model (2007).